Sustainable rice production in the Mekong River Delta: Factors influencing farmers’ adoption of the integrated technology package “One Must Do, Five Reductions” (1M5R - Connor, Melanie; Tuan, Le Anh; DeGuia, Anna H.; Wehmeyer, Helena (SAGE Publications, 2021)
Over the last few decades Vietnam has benefited from a rapid intensification of rice production ensuing high yields and economic gains. However, this has led to environmental degradation and adverse health effects. As a result, complex sustainable rice farming packages have been introduced but adoption still appears to be low. The present study aimed to investigate the factors affecting the adoption of sustainable rice farming practices combined in the national program “One Must Do, Five Reductions” (1M5R). Furthermore, a special focus was placed on identifying adoption constraints. Adoption was investigated by means of a survey questionnaire with 465 farmers in An Giang and Can Tho Province. Overall, results show that almost all farmers followed the requirements of pesticide reduction, post-harvest loss reduction, and the use of certified seeds. However, farmers had problems reducing their fertilizer use, water use, and seed rate. Results show that farmers perceive these practices to be difficult to implement, they do not fit farmers’ cropping pattern and the weather conditions hindered the implementation. The study further shows that ease of implementation, education, satisfaction and non-rice income are the main drivers for adopting the whole package. Adoption of the individual requirements is mainly driven by the ease of implementation and non-rice income for practices with lower adoption rates. This shows that farmers face physical adoption barriers, and that farmer satisfaction with the whole program is essential for a successful implementation. Results highlight the need for adoption monitoring and the continuation of extension services for the specific requirements specified under 1M5R.